Academic Repercussions and Adaptability as Predictors of Satisfaction with Studies in Peruvian University Students during COVID-19 - Ticona Arela, Kimberly Estefanny (2024)
The objective of this study was to determine the academic repercussions and adaptability to university life among post-secondary students in Peru during the COVID-19 pandemic. This research was also intended to determine whether these variables were predictors of satisfaction with their studies during the pandemic. A cross-sectional predictive study was conducted on an intentional, non-probabilistic sample of 570 university students of both sexes (women= 69.8%), between the ages of 18 and 44 years of age (M=21.12; SD=4.39). The participants were residents of Peruvian coast, mountain, and jungle regions who were enrolled in private and state universities and were assigned to faculties such as engineering, business, humanities, health sciences and education. In this case, students from the first to the fifth year of completed a questionnaire of adaptability to university life, a scale of academic repercussions and a brief scale of satisfaction with the studies. For data analysis, structural equation modeling (SEM) was performed, fulfilling goodness-of-fit measures. Based on the results, the predictive model has an adequate fit (χ2= 803.440, with 180 df, CFI = .930; IFI= .931; NFI=.912; CFI= .930; TLI=.919; RMSEA= .078), assuming that there is a statistically significant effect of academic repercussions and adaptability to university life on the variable, satisfaction with studies. It is concluded that the level of adaptability to virtual education and the perception of negative repercussions in the academic field predict the level of satisfaction with the studies of Peruvian university students in times of crisis such as that experienced due to the COVID-19 pandemic.